Blue-/Green-Light-Responsive Cyanobacteriochromes Are Cell Shade Sensors in Red-Light Replete Niches - Enomoto, Gen; Ikeuchi, Masahiko (iScience, 2020)
Cyanobacteriochrome (CBCRs) photoreceptors show various photochemical properties, but their ecophysiological functions remain elusive. Here, we report that the blue/green CBCRs SesA/B/C can serve as physiological sensors of cell density. Because cyanobacterial cells show lower transmittance of blue light than green light, higher cell density gives more green-light-enriched irradiance to cells. The cell-density-dependent suppression of cell aggregation under blue-/green-mixed light and white light conditions support this idea. Such a sensing mechanism may provide information about the cell position in cyanobacterial mats in hot springs, the natural habitat of Thermosynechococcus. This cell-position-dependent SesA/B/C-mediated regulation of cellular sessility (aggregation) might be ecophysiologically essential for the reorganization and growth of phototrophic mats. We also report that the green-light-induced dispersion of cell aggregates requires red-light-driven photosynthesis. Blue/green CBCRs might work as shade detectors in a different niche than red/far-red phytochromes, which may be why CBCRs have evolved in cyanobacteria. [Display omitted] •Blue- and green-light-sensing cyanobacteriochromes can be sensors of cell density•They may provide information about the cell position in microbial mats•Green-light-induced dispersion of aggregates needs red-light-driven photosynthesis•Cyanobacteriochromes might work in a different niche than red/far-red phytochromes Sensor; Biological Sciences; Microbiology